The Influence of Profitability, Leverage, and Firm Size on Firm Value in Automotive Companies Listed on the Indonesia Stock Exchange - I Wayan Mahesa Devana Giseh; Sahdan Saputra; Rini Anggriani (Citakonsultindo, 2025)
This study aims to analyze the effect of leverage, profitability, and firm size on firm value in automotive companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Firm value in this study is measured using Price to Book Value (PBV), leverage is measured by Debt to Asset Ratio (DAR), profitability is measured using Return on Assets (ROA), and firm size is represented by the natural logarithm of total assets (SIZE). The analytical method used is panel data regression with a fixed effect model, selected based on the results of the Chow test and Hausman test. The findings indicate that leverage (DAR) has a positive and significant effect on firm value, suggesting that the optimal use of debt can enhance investor confidence. Profitability (ROA) also has a positive and significant effect, indicating that firms with higher profitability tend to have better market value. Conversely, firm size (SIZE) has a negative and significant effect on firm value, implying that larger firms do not necessarily possess higher market value